Dinamika Butterfly Effect dalam Proses Pembuatan Kebijakan Dewan Perwakilan Rakyat Indonesia - Ferdian, Muhammad Ananda Denny; Nugroho, Taufiq (Shautuna: Jurnal Ilmiah Mahasiswa Perbandingan Mazhab, 2025)
The factor that influenced this article is the phenomenon of the Butterfly Effect given to the policies taken by the House of Representatives in Indonesia. The concept of the Butterfly Effect, which comes from the chaos theory, describes how the slightest change in the initial conditions will have a big and big impact later on. This study uses a qualitative approach, with case study analysis of several policies taken in the last period of the House of Representatives. Data was collected through interviews with members of the House of Representatives, analysis of documents, and studies of related literature. The findings of this study show that even small decisions regarding changes in budgeting or discussion of laws can have dynamic and long-term consequences both on society and the political system. For example, a delay in the promulgation of a law can cause dissatisfaction among the community, who may have started a social movement; Changes in budget policy also have an impact on various sectors of the economy. The study further found that communication between members of the House of Representatives and other stakeholders serves to magnify or minimize the impact of the policies taken. The fact that the political system is complex when viewed from the Butterfly Effect can result in better quality policy outputs and, thus, have a greater impact on society. It is hoped that the House of Representatives will be more careful in formulating policies by paying attention to the impact or long-term consequences of an action, optimizing the decisions taken by the leadership in the best interests of the community.